1988
DOI: 10.1002/jlcr.2580250711
|View full text |Cite
|
Sign up to set email alerts
|

2‐18F‐phenylalanine and 3‐18f‐tyrosine — synthesis and preliminary data of tracer kinetics

Abstract: SUMMARY2-1eF-phenylalanine and 3-leF-tyrosine were synthesized by direct electro hilic substitution of L-phenylalanine and Ltyrosine with PeF-acetylhypofluorite. obtained in 30 % radiochemical yield based on l$F-acetylhypofluorite within 60 min after the end of irradiation. In rat brain, 30 % of the radioactivity was fixed into acid-insoluble macromolecules and most of the free radioactivity existed as amino acids at one hour after 2-1eF-phenylalanine injection. In the case of 3-leF-tyrosine, significant amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…NMR spectrum of 6-FMT (À129.3 ppm, complex multiplet), 4-FMT (À138.4 ppm, doublet of doublet of doublets, 3 J(F À H 5 ) = 11.3 Hz, 4 J(F À H 6 ) = 4.2 Hz, 4 J(F À H 2 ) = 7.4 Hz), and 2-FMT (À142.2 ppm, doublet of doublets, 4 J(F À H 4 ) % 4 J(F À H 6 ) = 7.1 Hz) agree with those reported in the literature[29].…”
supporting
confidence: 93%
See 1 more Smart Citation
“…NMR spectrum of 6-FMT (À129.3 ppm, complex multiplet), 4-FMT (À138.4 ppm, doublet of doublet of doublets, 3 J(F À H 5 ) = 11.3 Hz, 4 J(F À H 6 ) = 4.2 Hz, 4 J(F À H 2 ) = 7.4 Hz), and 2-FMT (À142.2 ppm, doublet of doublets, 4 J(F À H 4 ) % 4 J(F À H 6 ) = 7.1 Hz) agree with those reported in the literature[29].…”
supporting
confidence: 93%
“…Although direct fluorination of L-phenylalanine results in the formation of 2-, 3-, and 4-fluoro-L-phenylalanine isomers [29], analytical HPLC and 19 F NMR spectroscopy indicated that fluorination with OF 2 did not result in the formation of fluorinated phenylalanine.…”
Section: Fluorination By Ofmentioning
confidence: 98%
“…Similar to the 4-substituted regioisomer, 2-[ 18 F]FPhe was prepared for the first time as early as the 1980s. 4,7 Several biological studies including the application of this tracer for imaging of cerebral gliomas, 8 for the investigation of neutral amino acid transport at the blood brain barrier, 9 and cerebral infarction in humans 10 were published. Unfortunately, a broader preclinical and clinical application is limited by the lack of reliable preparation procedures.…”
Section: Syn Thesismentioning
confidence: 99%